Analysis of Energy Performance on Envelope Ratio Exposed to the Outdoor. (2nd May 2018) - Lim, Hong Soo; Kim, Gon
Abstract : The shape of a building largely contributes to its energy consumption. The current study utilized metrics of surface-to-volume ratio, surface-to-floor ratio, area-to-perimeter ratio, and volume ratio to evaluate building energy performance. Also, the paper focused on the relation between the air-conditioned room and non-air-conditioned room. This approach affects both the design stages of the floor plan and the main designing factors that decide which spaces would become air-conditioned spaces such as those mostly occupied by residents or non-air-conditioned space such as staircases and elevators. The heating load and cooling load were calculated using the new equation based on the location of non-air-conditioned spaces and envelope ratio facing the outdoor. Both the width-depth ratio and envelope ratio were analyzed using the IES_V.E (Integrated Environmental Solutions Virtue Environment) program. It turns out that, as the non-air-conditioned spaces increase, both heating load and cooling load were reduced.